He kōrero kōrari : supervision for Māori : weaving the past, into the present for the future : a thesis submitted in fulfilment of the requirements for the degree of Masters of Philosophy (Social Work), Massey University - Eruera, Moana Margaret (Massey University, 2005)
This thesis uses a process of weaving together customs, values and traditions from the Māori world into current supervision requirements and realities of the present, as a guide for the provision of supervision for Māori in the future. Supervision for social work practitioners is critical in order to ensure best outcomes for clients, professional safety, practitioner learning and development and the implementation of accountability processes. Research on supervision has been completed overseas and more recently in Aotearoa with models of practice being developed which are more suited to our unique bicultural context in this country. Internationally and nationally indigenous and culturally appropriate models of supervision are now being recognised as necessary for the development of best supervision practice. Research on culturally appropriate models of supervision is relatively sparse and in particular research that provides a framework for indigenous peoples. This writing will contribute to the development of this body of knowledge, specifically examining a Kaupapa Māori framework for supervision. The principle context of this writing is indigenous culture, that is, this research analyses supervision whereby all participants share the same indigenous culture; the supervisor, supervisee and clients are all Māori in an interdependent relationship with an organisation. This qualitative research weaves together knowledge from a Māori worldview with the supervision experiences of Māori cultural advisors, Māori supervisors and Māori supervisees and supervision literature to formulate a Kaupapa Māori framework as a guide for the provision of Kaupapa Māori supervision for the future.
Keywords: Māori; Social workers; Māori Master's Thesis